JESUS CHRIST: THE NEXUS OF HEAVEN AND EARTH - Karwur, Edwin (STT INDONESIA MANADO, 2020)
The journal that is called Jesus Christ: The Nexus of Heaven and Earth is designed to anster the questions who Jesus Christ really really is, how does Jesus Christ relates to the concept of Israel’s God, to the Christian faith and to the world? These questions are answered through the an indept exegesis of John 1:51 based on a descriptive approach of the whole Gospel. The statement that Jesus expresses to Nathanael is quoted from the story of Jacub and his dream at Bethel, in order to declare that He is the meeting point of heaven and earth. This statement relates to what John says about Jesus in verse 14, where Jesus is stated as God who incarnated Himself on earth, and to what Jesus Himslef says in chapter 2:19 that He is the true Temple of God. The Creator has become a man. The glory of God is manifested on earth through His presence. As the meeting point or the bridge of heaven and earth, for John, Jesus is the way out for humanity to reconnect with God, as their heavenly Father in order for them to inherite the life in its truest sense, which is the life with a high quality of meaning. The life that is free from punishment and the life that is everlasting produced by the Holy Spirit, the very presence of God in the lives of His children. This kind of life is manifested in the morality of the believers and in their missions to the world.